Razvitie sub'ektnych svojstv licnosti v uslovijach sportivnoj dejatel'nosti - Gorskaja, G. B. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
In order to study the opportunities of sports as the educational environment promoting the becoming of subjectness, under the direction of the author the scientific project maintained by the Russian humanitarian scientific fund was carried out.